2018
DOI: 10.1136/emermed-2017-207214
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Japan Acuity and Triage Scale in adults: a cohort study

Abstract: Our study suggests an association of JTAS acuity with overall admission, ICU admission and ED length of stay, thereby demonstrating the predictive validity of JTAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In this study, the triage system demonstrated good predictive ability for in-hospital mortality, ICU admission and general ward admission prediction (AUC = 0.838, 0.830, 0.792 respectively). Similar results were shown in the validation studies of other triage systems [2,24]. A retrospective study to This study showed that the higher the urgency triage categories of patients, the greater their risk of hospitalization and progression to death.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, the triage system demonstrated good predictive ability for in-hospital mortality, ICU admission and general ward admission prediction (AUC = 0.838, 0.830, 0.792 respectively). Similar results were shown in the validation studies of other triage systems [2,24]. A retrospective study to This study showed that the higher the urgency triage categories of patients, the greater their risk of hospitalization and progression to death.…”
Section: Discussionsupporting
confidence: 84%
“…It is a global reality that emergency departments are overcrowded. In order to prioritize timely treatment for patients who present to emergency departments, triage scales have been implemented [1][2][3][4][5]. Hence, triage plays an important role in emergency medical care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in Japan have confirmed the usefulness of EWS in hospital and triage settings. [19][20][21][22] However, several countries require nationwide in-hospital EWS implementation, and in the UK, this has been widely used in prehospital settings, outpatients and emergency services. 4 Paramedics in Japan should directly request the hospital for ambulance acceptance on the scene.…”
Section: Open Accessmentioning
confidence: 99%
“…With great interest we have read the publication in the Emergency Medicine Journal from Kuriyama et al entitled ‘Validity of the Japan Acuity and Triage Scale (JTAS) in adults: a cohort study’ 1. We bring your attention to a few points that may enhance understanding of the validity of JTAS.…”
mentioning
confidence: 99%